2021
DOI: 10.1002/esp.5194
|View full text |Cite
|
Sign up to set email alerts
|

A framework for predicting abrasion rupture of crusts in wind erosion

Abstract: Crusts play a crucial role in the reduction or control of wind erosion. In this regard, the resilience and durability of crusts are of prime importance. Crusts have high resilience and durability against wind flow shear stresses; however, they are prone to abrasion induced by saltating particles. Therefore, estimating crust durability in abrasion rupture has practical importance. In this study, a cyanocrust and a biocemented sand crust were subjected to a controlled flux of saltating particles for different sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…In particular, particles carried by high-energy wind impacted the surface, and the crusts were destroyed due to long-term exposure to such impacts, so the surface formed more loose particles in the low wind energy environment. The wind erosion of the surface was further strengthened, and a large number of dust particles was released [22,23]. Finally, the surface was fully activated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, particles carried by high-energy wind impacted the surface, and the crusts were destroyed due to long-term exposure to such impacts, so the surface formed more loose particles in the low wind energy environment. The wind erosion of the surface was further strengthened, and a large number of dust particles was released [22,23]. Finally, the surface was fully activated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Deserts are widespread but contain only <5% clay and silt. Such sediments are transports over limited distances and are not a major source of dust [23,32]. The Gobi Desert was found to contain mainly 63-125 μm particles and to be finer than the average desert particle size (125-250 μm), leading to the generation of more dust [30].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of particle energy can be characterized by the CoR, which is related to the material properties, such as cohesion and elastic modulus (Lu & Bao, 2005). Cohesion and elastic modulus characterize the interparticle bonds of the material under an external force (Fattahi et al., 2021). Therefore, we experimentally measured the relevant mechanical parameters (Table 1), including the equivalent diameter ( d ), density ( ρ ), point load strength ( σ ) (Khandelwal & Singh, 2007), effective Young’s modulus ( E ), and cohesion ( P ) (Fattahi et al., 2021; Thornton, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…In aeolian sand flow, repeated impacts of particles create small microfractures on the surface, which extend from the point of applied local stress, accumulate over time, and weaken the interparticle bonds (Fattahi et al., 2021; Langston & Neuman, 2005; Neuman & Maxwell, 2002). In this process, the incident particles lose their kinetic energy to destroy the interparticle bonds of the material, resulting in a reduction of particle rebound speed.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that the saltation process could reduce crust strength and stiffness by up to 0.7 and 0.9, respectively, after 30 min of saltating (Fattahi et al, 2021). In addition to the effects of straw mulching on improvements of soil properties and wind direct impact, it may also significantly reduce the number of saltating particles and their continuous impact.…”
Section: Ridgementioning
confidence: 99%